Fundamentals of numerical reservoir simulation - Peaceman, Donald W. 1926- (Elsevier Scientific Pub. Co. : Distributors for the U.S. and Canada, Elsevier North-Holland, 1977)
Fundamentals of Numerical Reservoir Simulation.
Keywords: Oil reservoir engineering -- Mathematical models.; Oil reservoir engineering -- Data processing.; elektronické knihy; electronic books